2020
DOI: 10.3390/ani10020264
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Eggshell Colour on the Quality of Table and Hatching Eggs Derived from Japanese Quail

Abstract: The aim of the study was to evaluate table and hatching eggs of Japanese quails (Coturnix coturnix japonica) depending on the eggshell colour. The research was carried out in two stages, in terms of table eggs’ quality and their biological value as hatching eggs depending on the eggshell colour. In both stages, 300 Japanese quail eggs were used in each (600 in total) divided into two equal groups: with a brown-spotted shell, with a uniform shell in shades of blue. In the 1st stage, quality characteristics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(32 reference statements)
2
9
0
Order By: Relevance
“…Shell color (breed of hens) can influence the proportion of particular egg morphological elements, which is confirmed by previous observations [10] as well as data obtained by other authors [9]. Similar trends were also noticed in our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Shell color (breed of hens) can influence the proportion of particular egg morphological elements, which is confirmed by previous observations [10] as well as data obtained by other authors [9]. Similar trends were also noticed in our study.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, it was observed that eggs with dark brown shells (Mrs) were characterized by the highest shape index, so the data obtained by the authors indirectly agree with our own observations. However, these features may be related to the bird species, as studies on the eggshell color in Japanese quail [ 10 ] do not confirm these observations, although the shape index values obtained did not differ significantly between experimental groups (spotted vs. blue eggs).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, they also indicated that the effect of eggshell color on egg weight, eggshell mass, albumen weight, and yolk weight was not statistically significant. It was also pointed out that the shell color of Japanese quail eggs, blue or spotted, did not appear to affect their quality [ 29 ]; however, it can affect the hatching results and body weight of the obtained chicks of Japanese quails. Nevertheless, Taha [ 6 ] reported higher egg weight, egg length, and egg width in the black-spotted quail group than in the blue-spotted quail group.…”
Section: Discussionmentioning
confidence: 99%
“…The color of the eggshell has been reported to affect both its quality and biological value [ 8 10 ]. This is even though environmental influences such as relative humidity and storage time cannot be ruled out [ 11 ].…”
Section: Introductionmentioning
confidence: 99%